Unveiling the Connection: The Impact of Poverty Rate on Human Development Index in the Special Region of Yogyakarta Province Using the Almon Lag Model - Vatin, Kayyis; Kartikasari, Mujiati Dwi (Journal of Mathematics, Computations and Statistics, 2025)
The Human Development Index (HDI) is established as one of the main indicators included in the fundamental framework of regional development. Ideally, HDI, which serves as a benchmark for regional development, has a negative correlation with poverty conditions. Historical poverty can influence the current HDI based on elements of health, education, and a decent standard of living. The Special Region of Yogyakarta is the province with the second-highest HDI in Indonesia but has had the highest poverty rate in Java in recent years. The Almon Lag Model can analyze the impact of poverty on HDI by considering the distributed lag effect. This study aims to analyze the impact of the poverty rate on HDI over the past twenty-seven years. Based on the analysis, the best model utilizes a lag length of three years and a polynomial degree of two. The model has a Mean Absolute Percentage Error (MAPE) of 0.73%, indicating that the applied Almon Lag Model can make accurate predictions.